Pencarian Makna Hidup Siswa dari Keluarga Miskin di Kabupaten Wonosobo - Musofa Musofa; Casmini Casmini; Sutrisno Sutrisno (Psympathic : Jurnal Ilmiah Psikologi, 2019)
Students from poor families seems to have the ability to search the meaning of life. They have high enthusiasm in education. This study aims to explore the reasons of poor students in searching for life's meaning by choosing high school, concepts of meaning in life, and learning and its implications. The study used phenomenological-qualitative method.The participants were 21 students from poor families in reputable high school in Wonosobo. Data was collected through interviews and FGDs and was analyzed inductively. The results show that students from poor families understand the possibilities and benefits of achieving goals to be success in the future. Student balance is indicated by the determination of high goals and the hard work done in material, psychological and spiritual aspects.They are confident to move on and reflect the life’s meaning by act and pray.